2019
DOI: 10.3892/mmr.2019.10759
|View full text |Cite
|
Sign up to set email alerts
|

IL‑1β increases the expression of inflammatory factors in synovial fluid‑derived fibroblast‑like synoviocytes via activation of the NF‑κB‑mediated ERK‑STAT1 signaling pathway

Abstract: Interleukin (IL)-1β serves a crucial role in the progression of rheumatoid arthritis. Previous studies have indicated that the ERK/STAT1 signaling pathway may be involved in the inflammatory response in synovial fluid-derived fibroblast-like synoviocytes (sfd-FLSs). However, the molecular mechanisms underlying the pathological effects of the inflammatory factors induced by IL-1β in sfd-FLSs remain unclear. The aim of the present study was to investigate the IL-1β-mediated signaling pathways involved in the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Furthermore, our preliminary data showing activation of STAT1 in CIA SFs suggest coupling to STAT1 in conjunction with STAT3 signalling could explain the differential effects of ARNO in healthy and CIA SFs. Interestingly, simultaneous activation of NF-κB and STAT3 was found to enhance the inflammatory responses of non-immune cells ( 69 ) whilst an IL-1β activated ERK/STAT1 signaling pathway was proposed to promote NF−κB−mediated cytokine secretion in rat synovial fibroblasts ( 70 ). Therefore, ARNO could modulate SF-dependent inflammation by affecting the balance of STAT1/STAT3-NFκB pathways, a hypothesis we are currently investigating.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our preliminary data showing activation of STAT1 in CIA SFs suggest coupling to STAT1 in conjunction with STAT3 signalling could explain the differential effects of ARNO in healthy and CIA SFs. Interestingly, simultaneous activation of NF-κB and STAT3 was found to enhance the inflammatory responses of non-immune cells ( 69 ) whilst an IL-1β activated ERK/STAT1 signaling pathway was proposed to promote NF−κB−mediated cytokine secretion in rat synovial fibroblasts ( 70 ). Therefore, ARNO could modulate SF-dependent inflammation by affecting the balance of STAT1/STAT3-NFκB pathways, a hypothesis we are currently investigating.…”
Section: Discussionmentioning
confidence: 99%
“…In the next step, we investigated whether improvement of mitochondrial function will reduce the synthesis and expression of pro-inflammatory mediators in recipient FLS. IL1B plays crucial role in the progression of arthritis via modulation of NF-κB-mediated ERK/STAT signalling pathway while its inhibition decrease inflammation and facilitate the treatment of disease [ 4 ]. The present results suggested that mitotransfer decrease IL1B on the mRNA and protein expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of SI, FLSs are losing their protective and pro-regenerative cytological features, and become highly proliferative and metabolically active cells initiating various stress signaling pathways. Activated FSL have been shown to produce a broad range of proinflammatory cytokines including IL-1β, IL-6, IL-9, IL-15 or TNF-α while losing their immunomodulatory effect [ 4 ]. Recent data have demonstrated that activated FLS additionally release a wide plethora of caspases and metalloproteinases, that initiate unreversible joint degenerative changes.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is mediated almost completely by the proNGF present in SF, as the inhibition of proNGF binding to p75NTR led to an 80% reduction in IL-6 production. As it is well known that IL-1b enhances the expression levels of various inflammatory factors in RA-FLS through the activation of NF-kB/ERK/STAT1 axis, p38 mitogen-activated protein kinase (MAPK) and JUNK signaling pathways (22,32,33,47), we compared the effects of IL-1b and p75NTR neutralization on inflammatory cytokine production. We found that in RA-FLS the inhibition of p75NTR activation by LM11A-31 reduces the release of IL-6 to a similar extent as IL-1b inhibition by canakinumab.…”
Section: Discussionmentioning
confidence: 99%